Dynamic distribution modelling of the swamp tigertail dragonfly Synthemis eustalacta (Odonata: Anisoptera: Synthemistidae) over a 20‐year bushfire regime. (10th December 2022) - Goodman, Aaron M.; Kass, Jamie M.; Ware, Jessica
Abstract: Intensity and severity of bushfires in Australia have increased over the past few decades due to climate change, threatening habitat loss for numerous species. Although the impact of bushfires on vertebrates is well‐documented, the corresponding effects on insect taxa are rarely examined, although they are responsible for key ecosystem functions and services. Understanding the effects of bushfire seasons on insect distributions could elucidate long‐term impacts and patterns of ecosystem recovery. Here, the authors investigated the effects of recent bushfires, land‐cover change, and climatic variables on the distribution of a common and endemic dragonfly, the swamp tigertail ( Synthemis eustalacta ) (Burmeister, 1839), which inhabits forests that have recently undergone severe burning. The authors used a temporally dynamic species distribution modelling approach that incorporated 20 years of community‐science data on dragonfly occurrence and predictors based on fire, land cover, and climate to make yearly predictions of suitability. The authors also compared this to an approach that combines multiple temporally static models that use annual data. The authors found that for both approaches, fire‐specific variables had negligible importance for the models, while the percentage of tree and non‐vegetative cover were most important. The authors also found that the dynamic model outperformed the static ones, based on cross‐validation omission rate. Model predictions indicated temporal variation in area and spatial arrangement of suitable habitat, but no patterns of habitat expansion, contraction, or shifting. These results highlight not only the efficacy of dynamic modelling to capture spatiotemporal variables such as vegetation cover for an endemic insect species, but also provide a novel approach to mapping species distributions with sparse locality records. Abstract : The authors investigated the effects of bushfires, land‐cover change, and climate on the distribution of a common and endemic dragonfly, the swamp tigertail ( Synthemis eustalacta ), using dynamic and static model approaches. The authors found that fire‐specific variables had negligible importance for both dynamic and static models, while variables pertaining to tree and vegetated land cover were the most important. Model predictions indicated temporal variation in area and spatial arrangement of suitable habitat, but no patterns of habitat expansion, contraction or shifting.